2016
DOI: 10.1038/bonekey.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of pediatric bone strength

Abstract: Osteoporosis is one of the most common chronic forms of disability in postmenopausal women and represents a major health burden around the world. Bone fragility is affected by bone mineral density (BMD), and, one of the most important factors in preventing osteoporosis is optimizing peak bone mass, which is achieved during growth in childhood and adolescence. BMD is a complex trait resulting from environmental and genetic factors. Genome-wide association studies have discovered robust genetic signals influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
1
13
0
1
Order By: Relevance
“…Bone strength is influenced by mass, architecture and density, while the trajectory of bone strength accrual persists up to the age of about 18 years until peak bone mass (PBM) is reached [1,2]. Even though PBM is mainly explained by genetic determinants [3], it is also influenced by lifestyle-related factors such as mechanical loading, physical activity (PA), sedentary behaviour (SB) and nutrition [4,5]. Further, PBM is an important predictor of osteoporosis in adults, due to the age-related bone loss that occurs over time [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bone strength is influenced by mass, architecture and density, while the trajectory of bone strength accrual persists up to the age of about 18 years until peak bone mass (PBM) is reached [1,2]. Even though PBM is mainly explained by genetic determinants [3], it is also influenced by lifestyle-related factors such as mechanical loading, physical activity (PA), sedentary behaviour (SB) and nutrition [4,5]. Further, PBM is an important predictor of osteoporosis in adults, due to the age-related bone loss that occurs over time [6].…”
Section: Introductionmentioning
confidence: 99%
“…Early bone health is affected by several genetic disorders, such as Osteogenesis imperfecta (OI) [2224] and Ehlers-Danlos Syndrome (EDS) [22]. Having an improper collagen matrix also suppresses bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…A case series suggested that there is an association between parental Ehlers-Danlos/hypermobility syndrome and multiple fractures in infancy [27]. Genome-wide association studies indicate that pediatric bone mass is largely determined by genetics [22], and this aspect is thus of importance for MBD.A skeletal survey is recommended for the evaluation of suspected infant abuse as there is strong evidence to indicate that injury to the long bone and rib fractures are particularly liable to be due to abuse mechanisms [28]. Occult, clinically silent fractures are detected in 13%–31% of cases surveyed for suspected abuse [29].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of bone is obtained during childhood highlighting the need to characterize genetic factors that may contribute to paediatric bone phenotypes (Mitchell et al . ). As these genetic factors are identified, stable calcium isotope methods can evaluate the functional impact of these genotypes on parameters of calcium absorption and utilization.…”
Section: Introductionmentioning
confidence: 97%